Target মাধ্যমিক 2025
\(a(b-c)x^2+b(c-a)x+c(a-b)=0\) সমীকরণের বীজদ্বয় সমান হলে প্রমাণ কর \(\cfrac{1}{a}+\cfrac{1}{c}=\cfrac{2}{b}\)

যেহেতু, সমীকরণের বীজদ্বয় সমান ।
\(\therefore \) নিরূপক শূন্য ।
\(\therefore \{b(c-a)\}^2-4a(b-c)\cdot c(a-b)=0\)
বা, \(\{bc-ab)^2-4ac(b-c)(a-b)=0\)
বা, \(b^2c^2+a^2b^2-2ab^2c-4ac(ab-b^2\)

\(-ac+bc)=0\)



বা, \(b^2c^2+a^2b^2-2ab^2c-4a^2bc+4ab^2c\)

\(+4a^2c^2-4abc^2=0\)



বা, \(b^2c^2+a^2b^2+4a^2c^2+2ab^2c\)

\(-4a^2bc-4abc^2=0\)



বা, \((bc)^2+(ab)^2+(-2ac)^2+2.bc.ab\)

\(+2.ab.(-2ac)+2.(-2ac).bc=0\)



বা, \((bc+ab-2ac)^2=0\)
বা, \(bc+ab-2ac=0\)
বা, \(bc+ab=2ac\)
বা, \(\cfrac{1}{a}+\cfrac{1}{c}=\cfrac{2}{b}\) [উভয়পক্ষকে \(abc\) দ্বারা ভাগ করে পাই]
বা, \(\cfrac{1}{a}+\cfrac{1}{c}=\cfrac{2}{b}\,\,\) [প্রমাণিত]
Ganitsarani.in